Synthesis and electrochemical hydrogenation of RxTb2-xNi17 and Tb2Ni17-yMy phases (R = Y, Zr, La; M = Li, Mg) - Kordan, V.; Nytka, V.; Tarasiuk, I.; Kluziak, K.; Pavlyuk, V. (Physics and Chemistry of Solid State, 2024)
Alloys from the regions of existence of the solid solutions RxTb2-xNi17 and Tb2Ni17-yMy were synthesized by arc-melting with further annealing at 400 ºС. Quantitative and qualitative composition of alloys and powders of electrode materials was determined by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The Tb/R/Ni and Tb/Ni/Mg ratio in the samples was confirmed also by X-ray fluorescence spectroscopy. The cell parameters of RxTb2-xNi17 (x = 0.5) ternary phases are: a = 8.2987(9) Å, c = 8.0206(8) Å, V = 478.37(9) Å3 for R = Zr, a = 8.3161(6) Å, c = 8.0482(8) Å, V = 482.03(6) Å3 for R = Y and a = 8.3690(6) Å, c = 8.0560(7) Å, V = 488.66(6) Å3 for R = La. Tb atoms were partially substituted by Y, Zr and La atoms because of closeness of atomic radii size. Under experimental condition capacity parameters were 1.81 H/f.u. for the Zr-containing electrode, 2.29 H/f.u. for the Y-containing electrode and 2.31 H/f.u. for the La-containing electrode. In the case of Li,Mg co-doped electrodes we observed more than 2.5 H/f.u. Cell parameters of the Zr- and La-containing phases after hydrogenation increased isotropically. Synthesized hydrides can be interpreted as superstructures with the Tb2Mn17C2.5-type (filled-up of Th2Ni17). The Y0.5Tb1.5Ni17-based electrode demonstrates the potential corrosion at -0.540 V, electrodes with the compositions Zr0.5Tb1.5Ni17 and La0.5Tb1.5Ni17 show -0.413 V and -0.405 V, respectively. Li and Mg-codoped electrodes shoved the corrosion potential -0.410 V (Tb2Ni16.4Li0.2Mg0.4) and -0.550 V for Tb2Ni15.6Li0.6Mg0.8, respectively.